Hydrogeochemical characterization and quality assessment of groundwater resources in the Upper-Doab region of Uttar Pradesh, India - Gautam, Anant; Rai, Suresh Chand (Frontiers in Environmental Science, 2023)
The present study tries to delineate groundwater zones of the Upper-Doab region of Uttar Pradesh, India based on its suitability for the use of domestic and irrigational purposes considering the physicochemical parameters of groundwater samples (n ~ 70). The Upper-Doab region of Uttar Pradesh is bounded by the mighty rivers of Ganga and Yamuna in the east and west respectively. In the southwest, the region shares the boundary with the national capital of Delhi, which has led to an increase in the growth of urbanization and industrialization in the region. These factors have a great negative impact on the groundwater scenario of the region. Hydrogeochemical investigation reveals that the ionic dominance in the groundwater samples is in the order for HCO3 > Cl > SO4 > NO3 > F and Na > Mg > Ca > K. Chemical history of groundwater samples using piper trilinear diagram shows that Ca-Mg-HCO3 and Ca-Na-HCO3 type of groundwater is mostly found in this region. Gibb's plot reveals that rock-water interaction was dominantly controlling the ionic composition of the groundwater in the unconfined aquifer environment. Further, the bivariate plot of (SO4 + HCO3) vs. (Ca + Mg) reveals that the weathering of calcite and dolomite minerals present in the aquifer environment has largely attributed chemical character to the groundwater of the region. The groundwater zoning concerning its domestic and agricultural use reveals that the groundwater of Meerut, Muzaffarnagar, Baghpat, Ghaziabad, and Gautam Buddha Nagar districts have poorer quality of groundwater due to high electrical conductivity and higher concentration of nitrate which has a higher anthropogenic link. The evaluation of groundwater quality for irrigation using a single index value i.e., Composite Groundwater Quality Index for Irrigation (CGQII) makes this study different from the other hydrochemical investigations under similar hydrogeolocal aquifer conditions in the region. The study suggests that corrective measures like, strict implementation of untreated discharge of industrial effluents to the water or groundwater directly, creating awareness among farmers for lesser use of chemical fertilizers, and regular groundwater monitoring systems for quality analysis must be considered for a sustainable future of the region.